Geo-knowledge management and geoconservation via geoparks and geotourism - Farsani, Neda T.
A geopark as a new tourism destination contains a number of geological heritage sites. Geoparks as an innovation for the protection of natural and geological heritage are a network of sites for the transfer of Earth knowledge and the popularisation of geosciences. Moreover, geoparks play an important role in rural development through local involvement in geopark and geotourism activities. This paper discusses the role played by geoparks in the conservation and geo-knowledge management. To this end, 25 geopark strategies were analysed (20 in Europe and three in Asia: Malaysia, Japan and Iran; one in Australia and one in South America: Brazil). The results indicate that finding, introducing and establishing geosites are the first steps for geopark creation. Furthermore, involving local communities in the conservation of geoparks and providing educational projects are key factors in the knowledge management and preservation of geoparks as new tourist attractions.